Land use in mountain grasslands alters drought response and recovery of carbon allocation and plant‐microbial interactions. (20th December 2017) - Karlowsky, Stefan; Augusti, Angela; Ingrisch, Johannes; Hasibeder, Roland; Lange, Markus; Lavorel, Sandra; Bahn, Michael; Gleixner, Gerd
Abstract: Mountain grasslands have recently been exposed to substantial changes in land use and climate and in the near future will likely face an increased frequency of extreme droughts. To date, how the drought responses of carbon (C) allocation, a key process in the C cycle, are affected by land‐use changes in mountain grassland is not known. We performed an experimental summer drought on an abandoned grassland and a traditionally managed hay meadow and traced the fate of recent assimilates through the plant–soil continuum. We applied two 13 CO2 pulses, at peak drought and in the recovery phase shortly after rewetting. Drought decreased total C uptake in both grassland types and led to a loss of above‐ground carbohydrate storage pools. The below‐ground C allocation to root sucrose was enhanced by drought, especially in the meadow, which also held larger root carbohydrate storage pools. The microbial community of the abandoned grassland comprised more saprotrophic fungal and Gram(+) bacterial markers compared to the meadow. Drought increased the newly introduced AM and saprotrophic (A+S) fungi:bacteria ratio in both grassland types. At peak drought, the 13 C transfer into AM and saprotrophic fungi, and Gram(−) bacteria was more strongly reduced in the meadow than in the abandoned grassland, which contrasted the patterns of the root carbohydrate pools. In both grassland types, the C allocation largely recovered after rewetting. Slowest recovery was found for AM fungi and their 13 C uptake. In contrast, all bacterial markers quickly recovered C uptake. In the meadow, where plant nitrate uptake was enhanced after drought, C uptake was even higher than in control plots. Synthesis . Our results suggest that resistance and resilience (i.e. recovery) of plant C dynamics and plant‐microbial interactions are negatively related, that is, high resistance is followed by slow recovery and vice versa. The abandoned grassland was more resistant to drought than the meadow and possibly had a stronger link to AM fungi that could have provided better access to water through the hyphal network. In contrast, meadow communities strongly reduced C allocation to storage and C transfer to the microbial community in the drought phase, but in the recovery phase invested C resources in the bacterial communities to gain more nutrients for regrowth. We conclude that the management of mountain grasslands increases their resilience to drought. Abstract : In this study, on mountain grasslands, the management affected the response of plant carbon allocation and plant‐microbial interactions to drought and rewetting. Drought induced a shift to below‐ground carbon allocation, especially in the managed meadow, and increased the abundance of AM fungal markers, particularly in the more resistant abandoned grassland. After rewetting, strong plant‐bacterial interactions and increased nitrogen uptake were associated with a quick recovery of the meadow.